2010
DOI: 10.1177/0961203310381773
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders and psychological distress in systemic lupus erythematosus are not associated with disease activity

Abstract: Psychiatric diagnosis in patients with systemic lupus erythematosus (SLE) is controversial: variations have been reported in frequency, diagnostic assays, associations with disease activity, autoantibodies, and contributing social factors. Eighty-three consecutive non-selected Chilean patients with SLE were evaluated for: (i) 26 common mental disorders according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV), using the Mini-International Neuropsychiatric Interview (MINI-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 42 publications
4
58
0
3
Order By: Relevance
“…Studies on the prevalence of major depression in patients with rheumatologic disorders using structural clinical interviews have reported rates ranging from 9.5-16.2% in rheumatoid arthritis (37,38), 19% in systemic sclerosis (39) and 17-22.5% in systemic lupus erythematosus (36,40,41), with lifetime prevalence reported as high as 47% in women with lupus (42); less attention has been given to the prevalence of MDD in primary Sjö gren's syndrome, ankylosing spondylitis, psoriatic arthritis, mixed connective tissue disease, polymyalgia rheumatica, vasculitis, or other less frequent rheumatologic disorders. The results of the present study showed a pooled prevalence of MDD in patients with rheumatologic diseases of 25.4%, and although this rate may vary across the specific diseases, it provides an estimation of the depressed rheumatologic patients that a rheumatologist might expect in his or her everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the prevalence of major depression in patients with rheumatologic disorders using structural clinical interviews have reported rates ranging from 9.5-16.2% in rheumatoid arthritis (37,38), 19% in systemic sclerosis (39) and 17-22.5% in systemic lupus erythematosus (36,40,41), with lifetime prevalence reported as high as 47% in women with lupus (42); less attention has been given to the prevalence of MDD in primary Sjö gren's syndrome, ankylosing spondylitis, psoriatic arthritis, mixed connective tissue disease, polymyalgia rheumatica, vasculitis, or other less frequent rheumatologic disorders. The results of the present study showed a pooled prevalence of MDD in patients with rheumatologic diseases of 25.4%, and although this rate may vary across the specific diseases, it provides an estimation of the depressed rheumatologic patients that a rheumatologist might expect in his or her everyday practice.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Therefore, it can cause several neuropsychiatric syndromes, including depression. 6,7 Recent evidence suggests that the prevalence of depression in SLE patients is between 11.5% and 47%. [8][9][10][11][12][13] In addition, a recent study suggests that severity of depression increases with more severe disease activity of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…En 1994, nuestro grupo estudió la supervivencia de 218 enfermos con LES, con 5 años de duración de la enfermedad en promedio, 20% había presentado convulsiones o psicosis 17 . Recientemente, describimos una prevalencia de 42% de LESNP en 83 mujeres con LES (Tabla 1), 21% presentaba depresión mayor no relacionada con la actividad lúpica 14 .…”
unclassified
“…En un extremo se encuentran las convulsiones y la psicosis lúpica, que son manifestaciones claramente atribuibles al LES, tanto que forman parte de los criterios de clasificación diagnóstica de LES del ACR 20 , y si bien son poco frecuentes, se suelen presentar con enfermedad activa 21,22 . Al contrario, los síndromes NP como trastornos de ánimo y ansiosos, cefalea, y el déficit en el rendimiento cognitivo son atribuibles al lupus con más dificultad, pues pudiera ser coincidencia de dos enfermedades comunes, y además porque se observan con independencia de la actividad de la enfermedad 7,9,10,14,23,24 .…”
unclassified